PENGUATAN PEMBELAJARAN JARAK JAUH MELALUI WORKSHOP MEDIA PEMBELAJARAN INTERAKTIF DI ERA KENORMALAN BARU PADA GURU TK DAN PAUD SE KECAMATAN TANARA - Surtini Surtini; Ahmad Munawir (Gapenas Publisher, 2021)
Student Work and Community Service lectures conducted by students of Bina Bangsa University as agents of change can analyze problems that occur in the community and are able to focus on problem solving so as to provide change towards an independent and better society. Learning innovation and competency improvement are among the internal obstacles faced by educators in creating effective learning activities in pandemic times, in mastering and adjusting, learning with the development of science and technology. The method of implementation carried out in this devotional activity is through (1) socialization, interviews and analysis of problems that occur in the field of education, (2) the provision of information and training of interactive learning media. The results of this program add information and develop the skills required by educators in creating effective online learning